Medical Cannabis for Pediatric Moderate to Severe Complex Motor Disorders. (August 2018) - Libzon, Stephanie; Schleider, Lihi Bar-Lev; Saban, Naama; Levit, Luda; Tamari, Yulia; Linder, Ilan; Lerman-Sagie, Tally; Blumkin, Lubov
A complex motor disorder is a combination of various types of abnormal movements that are associated with impaired quality of life (QOL). Current therapeutic options are limited. We studied the efficacy, safety, and tolerability of medical cannabis in children with complex motor disorder. This pilot study was approved by the institutional ethics committee. Two products of cannabidiol (CBD) enriched 5% oil formulation of cannabis were compared: one with 0.25% δ-9-tetrahydrocannabinol (THC) 20:1 group, the other with 0.83% THC 6:1 group. Patients aged 1 to 17 years (n = 25) with complex motor disorder were enrolled. The assigned medication was administered for 5 months. Significant improvement in spasticity and dystonia, sleep difficulties, pain severity, and QOL was observed in the total study cohort, regardless of treatment assignment. Adverse effects were rare and included worsening of seizures in 2 patients, behavioral changes in 2 and somnolence in 1.